Rap and hip hop : the voice of a generation - Ayazi-Hashjin, Sherry (New York : Rosen Pub. Group, 1999)
Describes the art of rapping and the cultural phenomenon of hip hop, tracing its evolution from African and Caribbean traditions
Includes bibliographical references (p. 59), discography/videography (p. 60-61), and index
Keywords: Rap (Music) -- History and criticism -- Juvenile literature; Hip-hop -- United States -- Juvenile literature